First Molecular Detection ofDirofilaria immitisandD. repensin Dogs from Kyrgyzstan - Aydin, Mehmet Fatih; Altay, Kursat; Aytmirzakizi, Ayperi; Dumanli, Nazir (Springer Int Publ Ag, 2020)
Background Dirofilaria immitisandDirofilaria repensare the causative agents of cardiopulmonary and subcutaneous dirofilariosis, respectively. This neglected disease mainly seen in dogs, cats and wild carnivores is re-emerging recent years. No study was conducted on dirofilariosis in dogs in Kyrgyzstan. Purpose The goal of this study was to investigateDirofilariaspecies using PCR and sequencing in dogs from Kyrgyzstan. Method Dirofilariaspp. infection in dogs was screened via convential PCR and sequencing in 337 dogs from Kyrgyzstan. Result The overall prevalence ofDirofilariaspp. was 0.59% (2/337): DNA ofD. immitiswas detected in one sample and DNA ofD. repensin second positive sample. In second sample, parallel co-infection ofD. repenswithWolbachiawas also found. WhileD. immitissequence showed 98.70-100% similarity with previously reported sequences ofD. immitisfrom dog blood,D. repensshared 100% identity with other sequences ofD. repens. Conclusion These results provided first evidence forDirofilariaspp. in Kyrgyzstan and emphasized the veterinary and medical importance.
Keywords: Dirofilaria immitis; Dirofilaria repens; Kyrgyzstan; Dog; Vector-borne diseases; PCR; Sequencing